Analysis of the coupled dynamics of an offshore floating multi-purpose platform : part A - rigid body analysis - Li, L.; Collu, M.; Ruzzo, C.; Failla, G.; Abhinav, K. A.; Arena, F. (Volume 6: Ocean Space Utilization, 2019)
A multi-purpose platform (MPP) is an offshore system designed to serve the purposes of more than one offshore industry. Indeed, over the past decades, a number of industries have expanded, or are expanding, from onshore to offshore locations (renewables, aquaculture, tourism, mineral extractions, etc.), and the research on these type of platform is increasing. In the present work, a MPP able to accommodate wind turbines, wave energy converters, and aquaculture systems are considered. This work presents the first part (Part A) of the analyses of the dynamics of the floating support structure for this MPP, focusing on the rigid body dynamic response, while its complementary hydroelastic analysis is presented in Part B (OMAE2019-96282). The aim here is to assess the dynamic response of the platform with respect to the preliminary requirements imposed by the wind turbine, the aquaculture system, and the other ancillary systems. After describing the platform analyzed, and explaining the aero-hydro coupled model of dynamics approach adopted, two independent analyses are conducted, one using the SESAM package by DNV-GL, and another using ANSYS AQWA, in order to verify the results, in absence of experimental data. Considering a severe, but still operational, load case, the preliminary results seem to demonstrate that the chosen platform can satisfy the dynamics constraints imposed by the payload systems.